Use of SWOT Analysis Strategy in Developing School Quality at SD Negeri Hegarsari 02 Bogor - M. Arif Kurniawan; Dea Fitria (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Every school has a goal and requires the right strategy to achieve it. SD Negeri Hegarsari 02 Bogor conducted a SWOT analysis strategy, namely Strengths, Weaknesses, Opportunities and Threats to the development of school quality. This study aims to identify the state of the school from four points of view, namely, the strengths and weaknesses of the internal environment and the opportunities and threats from the external environment to develop school quality. This study uses a qualitativemethod that uses interview, observation, and documentation techniques in data collection. Primary data was conducted by interviewing principals and teachers, while secondary data was obtained by observing and documenting school profiles, teacher data, and inventory lists related to the use of the SWOT analysis strategy on the development of school quality at SD Negeri Hegarsari 02 Bogor. Based on the research results, SD Negeri Hegarsari 02 Bogor uses a SWOT analysis strategy that is carried out every year and even month as a school evaluation material. With the SWOT analysis, it is easier for schools to develop school quality. Schools have strengths based on 8 school quality indicators, namely graduation competency standards, content standards, process standards, educator and education standards, facilities and infrastructure standards, management standards, financing standards, and assessment standards. This is a strength in developing the quality of schools. SD Negeri Hegarsari 02 Bogor also has weaknesses, but schools are able to minimize these weaknesses. In addition, there is an opportunity that can be achieved by SD Negeri Hegarsari 02 Bogor to become a force in developing school quality, and there is a threat to schools, but this can be overcome by SD Negeri Hegarsari 02 Bogor.